Diferensiasi Bahasa berdasarkan Gender pada Sidang Mediasi di Pengadilan Agama Bandung: Suatu Kajian Sosiolinguistik - Gipari, Nenden Liska (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This study explores language differentiation based on gender that occurs during mediation sessions at the Religious Court of Bandung. It examines two divorce hearings involving plaintiffs and defendants from different ethnic backgrounds to observe the influence of cultural background on discourse in the mediation process. Data were collected over five weeks, from May 21 to June 17, 2024, with an in-depth analysis of two hearings representing diverse social and cultural contexts. The first hearing involved a Sundanese plaintiff and a Malay defendant, while the second hearing included a Sundanese plaintiff and a Minangkabau defendant. The analysis results show significant differences in the use of linguistic features between women and men. Women tend to use features such as hedges, intensifiers, and tag questions, reflecting uncertainty and an effort to convey politeness. In contrast, men more frequently discuss masculine topics and use more direct language. Social factors such as differences in education and cultural background influence how both parties communicate in formal contexts. Additionally, the mediator plays a crucial role in creating a safe and constructive dialogue space. These findings highlight the dynamics of gender and culture in courtroom communication and the importance of understanding the social context in the mediation process to achieve effective solutions.